Changing the Angle of Vision: Astrolabe Dials on Astronomical Clocks - Oestmann, Günther (Medieval encounters, 2017)
From the middle of the fourteenth century until the Early Modern period, several monumental astronomical clocks were erected in Europe, and on many of them astrolabe dials were placed. On a group of earlier clocks, “southern astrolabes” (i.e. with stereographic projection from the North Pole) were employed, whereas later examples show a “northern astrolabe” (i.e., a stereographic projection from the South Pole), which is commonly used on portable astrolabes. The material and textual evidence as well as reasons for this change shall be examined. Moreover, the question of transmission of special variants of stereographic projection from East to West will be discussed.